Internet perceptions among older adults in Sweden - Bergström, Annika (Frontiers in Human Dynamics, 2023)
The digital inequality is still present after decades of development and diffusion of digital media. Age is one of the most important factors predicting access, use, skills, and outcomes, which is somewhat paradoxical as information and communication technologies can create opportunities for older adults to sustain independent living. To increase understanding of older adults' online engagement, this study focuses on perceptions of the internet usage and how it can be a useful tool in everyday life. Based on representative survey (n=841), analyses point to decreasing support for the internet with increasing age -also within the group of 66 to 85 years old. There are significant correlations between perceptions and internet experience, whereas sociodemographic factors have weak explanatory power. Interestingly, large shares of older adults do not have any opinion of the internet, which could partly explain the persistence of the digital divide and difficulties to increase digital literacy.